Fluoride Distribution in Sound and Carious Root Tissues of Human Teeth - Shu, M.; Pearce, E. I. F.; Sissons, C.H.; Coote, G.E.; Miller, J. H. (Caries research, 1998)
Proton probe analysis has been used to provide for the first time quantitative F concentration data in carious root tissues from subjects consuming water containing 1 ppm F. In small lesions at the neck of the tooth with minimal tissue loss the F concentration was significantly higher at the outer lesion edge than at the outer edge of adjacent sound root tissue. In one sample with high F values the lesion edge had 19,000 ppm F and the adjacent sound root surface 5,400 ppm F (μg F/g apatite). In large lesions with extensive cavitation F was again concentrated in the outer edge of the lesion and was significantly higher (1,800–4,100 ppm) than in adjacent sound inner dentine (190–290 ppm). Fluoride concentrations varied markedly along the outer edge of both normal and carious root tissues. Fluoride increase at the lesion edge is not an effect of tissue shrinkage but probably a result of remineralisation events during caries. This additional F may be expected to increase tissue resistance to further acid attacks.